Conservative strategy in infantile fibrosarcoma is possible: The European paediatric Soft tissue sarcoma Study Group experience. (April 2016) - Orbach, Daniel; Brennan, Bernadette; De Paoli, Angela; Gallego, Soledad; Mudry, Peter; Francotte, Nadine; van Noesel, Max; Kelsey, Anna; Alaggio, Rita; Ranchère, Dominique; De Salvo, Gian Luca; Casanova, Michela; et al.
Abstract: Background: Infantile fibrosarcoma (IFS) is a very rare disease occurring in young infants characterised by a high local aggressiveness but overall with a favourable survival. To try to reduce the total burden of therapy, the European pediatric Soft tissue sarcoma Study Group has developed conservative therapeutic recommendations according to initial resectability. Material and methods: Between 2005 and 2012, children with localised IFS were prospectively registered. Initial surgery was suggested only if possible without mutilation. Patients with initial complete (IRS-group I/R0) or microscopic incomplete (group II/R1) resection had no further therapy. Patients with initial inoperable tumour (group III/R2) received first-line vincristine-actinomycin-D chemotherapy (VA). Delayed conservative surgery was planned after tumour reduction. Aggressive local therapy (mutilating surgery or external radiotherapy) was discouraged. Results: A total of 50 infants (median age 1.4 months), were included in the study. ETV6-NTRK3 transcript was present in 87.2% of patients where investigation was performed. According to initial surgery, 11 patients were classified as group I, 8 as group II and 31 as group III. VA chemotherapy was first delivered to 25 children with IRS-III/R2 and one with IRS-II/R1 disease. Response rate to VA was 68.0%. Mutilating surgery was only performed in three cases. After a median follow-up of 4.7 years (range 1.9–9.0), 3-year event-free survival and overall survival were respectively 84.0% (95% confidence interval [CI] 70.5–91.7) and 94.0% (95% CI 82.5–98.0). Conclusions: Conservative therapy is possible in IFS as only three children required mutilating surgery, and alkylating or anthracycline based chemotherapy was avoided in 71.0% of patients needing chemotherapy. VA regimen should be first line therapy in order to reduce long term effects. Highlights: Prospective European study of 50 patients with infantile fibrosarcoma (IFS). IFS shows a very good response to vincristine-actinomycin-D chemotherapy. Mutilating surgery could be avoided in 94.0%. Conservative treatment approach is feasible in without jeopardising survivals. Good compliance with treatment guidelines.